Modulating Activity through Defect Engineering of Tin Oxides for Electrochemical CO2 Reduction. Issue 18 (4th July 2019) - Daiyan, Rahman; Lovell, Emma Catherine; Bedford, Nicholas M.; Saputera, Wibawa Hendra; Wu, Kuang‐Hsu; Lim, Sean; Horlyck, Jonathan; Ng, Yun Hau; Lu, Xunyu; Amal, Rose
Abstract: The large‐scale application of electrochemical reduction of CO2, as a viable strategy to mitigate the effects of anthropogenic climate change, is hindered by the lack of active and cost‐effective electrocatalysts that can be generated in bulk. To this end, SnO2 nanoparticles that are prepared using the industrially adopted flame spray pyrolysis (FSP) technique as active catalysts are reported for the conversion of CO2 to formate (HCOO − ), exhibiting a FEHCOO − of 85% with a current density of −23.7 mA cm −2 at an applied potential of −1.1 V versus reversible hydrogen electrode. Through tuning of the flame synthesis conditions, the amount of oxygen hole center (OHC; SnO●) is synthetically manipulated, which plays a vital role in CO2 activation and thereby governing the high activity displayed by the FSP‐SnO2 catalysts for formate production. The controlled generation of defects through a simple, scalable fabrication technique presents an ideal approach for rationally designing active CO2 reduction reactions catalysts. Abstract : The controlled generation of defects through a simple, scalable fabrication utilizing flame spray pyrolysis presents a promising approach for rationally designing active CO2 reduction reactions catalysts. In this work, it is demonstrated that by manipulating the defect sites in tin oxide electrocatalysts, the activity of the catalysts for the selective conversion of CO2 into formate can be improved.